Spatial frequency channels depend on stimulus bandwidth in normal and amblyopic vision: an exploratory factor analysis - Reynaud, Alexandre; Min, Seung Hyun (Frontiers in Computational Neuroscience, 2023)
The Contrast Sensitivity Function (CSF) is the measure of an observer’s contrast sensitivity as a function of spatial frequency. It is a sensitive measure to assess visual function in fundamental and clinical settings. Human contrast sensitivity is subserved by different spatial frequency channels. Also, it is known that amblyopes have deficits in contrast sensitivity, particularly at high spatial frequencies. Therefore, the aim of this study was to assess whether the contrast sensitivity function is subtended by the same spatial frequency channels in control and amblyopic populations. To determine these spatial frequency channels, we performed an exploratory factor analysis on five datasets of contrasts sensitivity functions of amblyopic and control participants measured using either gratings or noise patches, taken from our previous studies. In the range of 0.25 to 10 c/d, we identified two spatial frequency channels. When the CSF was measured with noise patches, the spatial frequency channels presented very similar tuning in the amblyopic eye and the fellow eye and were also similar to what was observed in controls. The only major difference was that the weight attributed to the high frequency channel was reduced by approximately 50% in the amblyopic eye. However, when the CSF was measured using gratings, the spatial frequency channels of the amblyopic eye were tuned towards lower spatial frequencies. These findings suggest that there is no mechanistic deficit for contrast sensitivity in amblyopia and that amblyopic vision may just be subjected to excessive internal noise and attenuation at higher spatial frequencies, thereby supporting the use of therapeutic strategies that involve rebalancing contrast.